Relationship between 25(OH)D2, 25(OH)D3 and core symptoms in autism spectrum disorder - Jia, Liu; Hongfei, Du; Deyun, Zhao (Frontiers in Pediatrics, 2025)
BackgroundThis study intended to explore the levels of 25(OH)D2 and 25(OH)D3 in children with autism spectrum disorder (ASD) and analyzed the correlation between 25(OH)D2, 25(OH)D3 levels and ASD core symptoms, children development.MethodsA total of 208 children with ASD who were diagnosed in hospital from January 2021 to December 2023 were selected as the ASD group. 208 children for routine physical examination were selected as the control group. The contents of 25(OH)D2 and 25(OH)D3 in serum were detected by high-performance liquid chromatography tandem mass spectrometry (HPLC-MS/MS) method. The ASD group were assessed by Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS) and Gesell Development Schedule (GDS). Meanwhile, the correlations between the levels of 25(OH)D2, 25(OH)D3 and ABC, CARS, GDS in ASD children were analyzed.ResultsThe serum levels of 25(OH)D2 and 25(OH)D3 in the blood of the children in the ASD group were significantly lower than those in the control group (P < 0.050). There was no significant correlation between serum 25(OH)D2 levels and ABC, CARS, in children with ASD (P > 0.050). However, there were lower 25(OH)D3 levels were associated with more severe ASD symptoms (P < 0.050). The higher level of 25(OH)D2 was significantly correlated with lower adaptive behavior and personal-social of GDS (P < 0.050). The higher level of 25(OH)D3 was significantly correlated with higher adaptive behavior, fine motor and personal-social of GDS (P < 0.050).ConclusionsThe levels of 25(OH)D2 and 25(OH)D3 in ASD children were significantly lower than those in healthy children. Besides, the study identified distinct roles for vitamin D isoforms including 25(OH)D2 and 25(OH)D3 in ASD pathophysiology. 25(OH)D2 showed selective impairments in adaptive behavior and personal-social behavior. 25(OH)D3 exhibited strong inverse correlations with symptom severity and positive associations with adaptive/fine motor/personal-social.